Application Of Articulation Learning Model to The Eye Entrepreneurship Lessons in Class Xi Majoring In Industrial Electronics Engineering SMK Negeri 2 Sungai Penuh - Andri Yuliandi; Ambiyar; Mahesi Agni Zaus (Indonesia Journal of Engineering and Education Technology (IJEET), 2024)
Student learning outcomes are a benchmark for the success of the educational process, but not all learning outcomes are satisfactory, including in the Entrepreneurship subject because students are less active in the learning process. So research was carried out using the Articulation learning model in the Entrepreneurship subject in class This research uses experimental research methods. Which has an experimental class and a control class. Based on the results of this research, it is learning using the articulation learning model had an effect on the learning outcomes of class XI at SMK Negeri 2 Kota Sungai Full Department of industrial electronics engineering for the 2023/2024 academic year